DETERMINATION OF AN OBVIOUS FACTUAL ERROR IN A CADASTRAL MAP: DETERMINATION OF AN OBVIOUS FACTUAL ERROR IN A CADASTRAL MAP - Niyazi-Yusuf, Mirem; Kirilova, Krasimira; Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The maps created of reinstated property after 1990 contain numerous errors. These errors have been transferred from the existing cadastral plans, comassation plans, land subdivision plan, aerial photo plans and a large-scale topographic maps created in the years 1964-1968. For the creation of maps of the reinstated property, the sources described above were used directly, without repeated aerial photography or deciphering of the objects as well as without the conduction of direct geodetic measurements [6, 8]. The presence of an obvious factual error is a relatively common phenomenon in the cadastral map. The same applies mainly to linear objects and it is quite possible to remove these errors. These errors can be corrected via separate projects for the specific errors, as well as via projects affecting a large part of land territory and even an entire land territory.